The Effectiveness of Using Telegram App in Learning English as a Foreign Language among Secondary School Students - Almansour, Shaden Mohammed (Journal of Educational and Psychological Sciences, 2022)
Digital media technology including social media applications have become an inseparable part of most students’ everyday life. The increasing advancement of new technologies has made it easier to integrate them into the education system. Today, learners can use social media applications such as Telegram, Twitter, or Instagram to improve their English language skills and knowledge. This study aims to investigate Saudi secondary school students’ perceptions and attitudes towards the use of a social media application called (Telegram) as a tool to learn English as a foreign Language (EFL). The research follows a qualitative methodology in which 15 secondary school students were interviewed online to recount their experiences of using Telegram app as a means of supporting their learning of EFL. A thematic analysis technique was used to analyze data obtained from the interviews. Findings revealed that most students perceived Telegram app to be an effective tool for English language learning specifically in the writing skill. These findings played a critical role in helping the researcher draw the argument about the effectiveness of Telegram app in teaching and learning English language.